Notes to Philosophy 167: Class 14 -- Newton's De Motu Corporum, Version 3 -- Part 10. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Drafts of New "Laws": The Third Law -- Further Drafts of Definitions: The Concept of Mass -- The Law of Gravity Emerges.; Generally corresponds to the video segment: Class 14, Part 10.